2015
DOI: 10.1111/1756-185x.12784
|View full text |Cite
|
Sign up to set email alerts
|

Pain intensity, temperament traits and social support as determinants of trauma symptoms in patients suffering from rheumatoid arthritis and low‐back pain

Abstract: The importance of temperament traits, social support and trauma symptoms should be taken into an account in psychotherapy accompanying pharmacotherapy for pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…For specific chronic pain, pain intensity can be considered as one of the factors for trauma symptoms in patients with CLBP or arthritis . Additionally, lower‐level pain intensity was observed to be 1 of only 2 factors independently related to decreased levels of distress in patients with rheumatoid arthritis .…”
Section: Discussionmentioning
confidence: 99%
“…For specific chronic pain, pain intensity can be considered as one of the factors for trauma symptoms in patients with CLBP or arthritis . Additionally, lower‐level pain intensity was observed to be 1 of only 2 factors independently related to decreased levels of distress in patients with rheumatoid arthritis .…”
Section: Discussionmentioning
confidence: 99%
“…There was a lack of correlation of Igbo-MSPSS with pain intensity, self-reported back pain-specific disability and life activities subscale of the Igbo-WHODAS (generic self-reported disability). Evidence suggests that social support may not be directly associated with pain intensity and self-reported back pain-specific disability in people with CLBP (Rzeszutek et al, 2016;Suner, 2007), but may be directly associated with psychological outcomes such as depression and unhelpful coping strategies, such as kinesiophobia, and catastrophising in people with CLBP (Campbelll, Wynne-Jones, & Dunn, 2011;López-Martínez, Esteve-Zarazaga, & Ramírez-Maestre, 2008;McKillop, Carroll, Jones, & Battié, 2017). Furthermore, the life activities subscale of the WHODAS (Igwesi-Chidobe et al, 2020) measures the ease or difficulty with which common household tasks and work/school activities are performed, which are the concepts mainly captured in self-reported back pain-specific disability measured with the RMDQ Table 3 Spearman's correlation analyses between Igbo-MSPSS and intensity of pain (BS-11), performance-based disability (BPS), self-reported back pain-specific disability (Igbo-RMDQ), selfreported generic disability (Igbo-WHODAS and its subscales) Igwesi-Chidobe et al, 2019;Roland & Morris, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore expected to have better correlation with getting along and cognition subscales of the Igbo-WHODAS whose constructs appear more closely associated with social support than the other Igbo-WHODAS subscales. The literature suggests that social support is not significantly correlated with pain intensity and pain-related disability in people with CLBP (Rzeszutek, Oniszczenko, Schier, Biernat-Kałuża, & Gasik, 2016), therefore the Igbo-MSPSS is expected to have no significant correlation with Igbo-BS-11, Igbo-RMDQ, and the BPS.…”
Section: Validitymentioning
confidence: 99%
“…Of important note is the possible influence of culture on personality trait which can both influence pain perception and expression including pain coping strategies [17][18][19][20]. People of African ancestry are said to report higher levels of pain unpleasantness, emotional response to pain and pain behavior, in response to similar levels of pain intensity than other ethnic groups [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The original authors found that the eight subscale had an unacceptable level of internal consistency and recommended the use of the 42-item version of the CSQ as the standard CSQ [23]. CSQ consists of seven subscales with six items each: (diverting attention [items 3,9,12,26,27,38], reinterpreting pain sensation [items 1,4,10,16,29,41], catastrophising [items 5,11,13,25,33,37], ignoring pain sensations [items 17,19,21,24,30,35], praying or hoping [items 14,15,18,22,28,36], coping self-statements [items 6, 8, 20, 23, 31, 32] and increased behavioural activities [items 2, 7, 34, 39, 40, 42]). Each item has a numeric rating scale ranging from 0 (never do that) to 6 (always do that).…”
Section: Outcome Measures Coping Strategies Questionnaire (Csq)mentioning
confidence: 99%